Contemporary Looks and Museographic Approaches from the Local in the Exhibition Obreras. Trabajo en el frigorífico y barrio Saladillo - Olivari, María Cecilia (2021)
The article attempts to explore the museographic and visual strategies involved in the exhibition “Obreras: Trabajos en el frigorífico y barrio Saladillo.” (Argentina: Museo de la Ciudad de Rosario Wladimir Mikielevich, 2019). The exploration of this case opens an alternative line of curatorial and museographic practices with a gender perspective applied to history, that also focuses on meaningful experiences at the local level. From a transdisciplinary perspective, this case will be addressed based on a museology of the idea (García Blanco, 1999) expanded to the thematic turns (Guasch, 2016) and the constellations of images (Piñero, 2013; Giunta, 2016), seeking to investigate the use of museographic resources and typologies. This approach to the ways of exhibiting today (Panozzo & Olivari, 2020), allows to contemplate different means to challenge the visiting public in order to generate an amplified museal experience.